Fear, economic consequences, hunting competition, and distrust of authorities determine preferences for illegal lethal actions against gray wolves (Canis lupus): a choice experiment among landowners in Jutland, Denmark - Højberg, Peter Lyhne (Crime, law and social change, 2017)
After a 200-year absence, the gray wolf recently re-immigrated to Denmark. Where humans and wolves coexist, there is potential for conflict. Using an online survey, we elicit information on attitudes and preferred responses to the presence of wolves among 1500 landowners in rural Jutland. Relying on random utility theory, we used a choice experiment, where respondents were asked to choose between hypothetical scenarios designed to reduce the sensitivity of the subject and thereby reveal whether landowners would respond by illegal actions. We also evaluate the determinants of preferences for these actions. The majority of the sample exhibited a negative attitude towards wolves and the choice experiment revealed that 60% of the sample preferred illegal measures, over moderate measures, whereas the remaining sample preferred to do nothing. A latent class model grouped respondents in four segments based on similarities of preferences. Preference for illegal lethal actions were found among four groups concerned about; (1) negative economic impact; (2) competition over game; (3) safety of humans and domestic animals, and; (4) lack of trust in authorities. Our results do not imply that 60% of landowners in Jutland will illegally kill wolves. However, negative attitudes, particularly when combined with a divide between rural- and urban communities, may promote disregard for regulations and illegal actions against problem species. The rural population should be informed and involved to improve the legitimacy of management decisions. In addition, changes in attitudes toward wolves should be monitored. The results are interpreted in terms of anthropocentrism and speciesism.